Raft Thickness Rational Design for Megatall Skyscrapers: Case Studies - Van, Hoa Cao (Engineering, Technology & Applied Science Research, 2024)
The design process for tall buildings involves three main steps: Estimating roughly the sizes of foundation and superstructure components, verifying the determined sizes with full consideration of the interactions between soil, piles, raft, and superstructure to ensure the bearing capacity and deformation of all elements, and optimizing the design with parametric analysis. However, the thickness of the rafts in existing buildings appears to be very thick and varies to the point of confusion. It is noticeable that some buildings have a considerable height but a relatively small raft thickness and vice versa. To address this issue, a simplified graphical method is proposed to determine the raft thickness for the initial design phase. As megatall skyscrapers become increasingly common, a more comprehensive study of rafts is necessary. This article explores the process of designing and constructing rafts for tall and megatall skyscrapers. The study aims to validate and extend the graphical method and establish a basis for the raft thickness optimization process. The research shows that the number of floors strongly affects the thickness of the rafts. However, the elastic modulus is significantly influenced when the ratio of the raft thickness to the number of floors is less than 5% and vice versa.